급성호흡부전증후군에서 Prone Position의 호흡 및 혈류역학적 효과 - 임채만; Chae Man Lim; 고윤석; Youn Suck Koh; 정복현; Bok Hyun Jung; 이상도; Sang Do Lee; 김우성; Woo Sung Kim; 김동순; Dong Soon Kim; et al. (Tuberculosis and respiratory diseases, 1997)
Background : Prone position improves oxygenation in some patients with ARDS. According to some authors, prone position can also improve the deteriorated hemodynamics induced by PEEP. But these respiratory and hemodynamic effects of prone position has not yet been fully established. Methods : Twentythree consequtive patients with ARDS(M : F= 11 : 12, $62.1{±}20.8yrs$) were the subjects for this study. ABGA, static compliance of the respiratory system, mean arterial pressure and pulse rate were obtained in supine position and at 5min, 0.5h and 2h of prone position. Positive respiratory response was defined as 20mmHg or more increase in $PaO_2/FIO_2$ within 2h of prone position. Early of late respiratory responses were defined if the positive response was observed within of after 3 day of ARDS onset, respectively. Positive hemodynamic response was defined as 10mmHg or more increase in mean arterial pressure at 5min of prone position. Results : Fifteen patients (65%) showed positive respiratory response. In the respiratory responders, $PaO_2$ was $69.8{±}17.6mmHg$ in supine position, $83.2{±}22.6mmHg$ in prone position 0.5h, $96.8{±}22.7mmHg$ in prone position 2h(p<0.001), and $PaO_2/FIO_2$ was $108{±}41mmHg$, $137{±}57mmHg$, $158{±}50mmHg$, respectively(p=0.001). Age, sex, cause of ARDS, supine $PaO_2$ and $PaO_2/FIO_2$ were not different between the respiratory responders and the nonresponders. The respiratory responders, however, showed higher mean arterial pressure than the nonresponders($91.1{±}13.1mmHg$ vs. $76.0{±}18.7mmHg$, p=0.035), and tendency of higher survival rate(9/15 vs. 2/8, p=0.074). Static compliance of the respiratory system was decreased in prone position 0.5h($28.4{±}7.9ml/cm$ $H_2O$ vs. $23.8{±}7.6ml/cm$ $H_2O$, p=0.007). The overall rate of early response(n=23) and late response(n=11) were similar(14/23 vs. 7/11, p>0.05). But patient without early response showed late response only in 25%(1/4), while patient with early response showed late response in 85.7%(6/7)(p=0.072). Five patients(22%) showed positive hemodynamic response, two of them being respiratory nonresponders. There were no differences in the baseline mean arterial pressure or the level of PEEP applied in supine between the hemodynamic responders and the hemodynamic nonresponders. Conclusions : Prone position either improved oxygenation or increased arterial pressure in significant proportion of patients with ARDS. And the respiratory response to prone position was thought to be determined in the early stage of ARDS. 배 경 : 급성호흡부전증후군에서 배측 폐는 복측 폐에 비해 이환 정도가 심하여 기계호흡시 PEEP 사용에도 폐포 모집이 어려운 것이 알려져 있고 이러한 상태에서 prone position은 이환이 심한 배측 폐의 국소 환기를 향상시키고 동맥혈산소분압의 호전을 가져온다는 보고들이 있으나 아직 prone position 의 호흡생리학적 효과나 혈류역학적 효과가 완전히 정립되지 않았다. 방 법 : 급성폐손상 점수 평균 2.5 이상인 ARDS 환자 23명(남 : 여 =11 : 12, 연령 $62.1{±}20.8$세)을 대상으로 먼저 supine position에서 호흡 지표로 동맥혈가스분석, 총호흡기계 정적 탄성과 혈류역학적 지표로 평균 동맥압, 분당 심박수 등을 얻은 뒤 prone position으로 전환하였다. Prone position 5분에 동일한 혈류역학적 지표, 0.5 및 2시간에 호흡 지표를 얻었으며, 2시간까지의 $PaO_2/FIO_2$ 비가 supine position에 비해 20mmHg 이상 증가한 경우를 양성 호흡반응, prone 5분의 평균동맥압이 supine position에 비해 10mmHg이상 증가한 경우를 양성 혈류역학적반응으로 각각 정의하였다. 결과 : 1. 양성 호흡반응 대상 ARDS 환자 중 65%(15/23)가 양성 호흡반응을 보였고 양성 반응자는 비반응자에 비해 연령, 남녀비, ARDS 유발 원인, supine position에서의 $PaO_2/FIO_2$비, Cst, rs 등은 차이가 없었으나 평균동맥압이 더 높고($91.1{±}13.1mmHg$ vs. $76.0{±}18.7mmHg$, p=0.035), 생존율이 높은 경향을 보였다(9/15 vs. 2/8, p=0.074). 양성 호흡반응자의 supine, prone 0.5 및 2시간의 $PaO_2$는 각각 $69.8{±}17.6mmHg$, $83.2{±}22.6mmHg$, $96.8{±}22.7mmHg$(p<0.001), $PaO_2/FIO_2$비는 각각 $108.1{±}40.5mmHg$, $137.3{±}60.0mmHg$, $157.7{±}50.0mmHg$로 증가하였다(p=0.001). 2. 양성 혈류역학적반응 Prone position시 평균 동맥압이 10mmHg이상 증가한 경우는 22%(5/23)이었고 이 중 2명은 양성 호흡반응이 없는 환자였다. 양성 혈류역학적반응을 보인 환자와 보이지 않은 환자 사이에 기저 평균동맥압($77.1{±}11.1mmHg$, $89.8{±}16.6mmHg$, p=0.099)이나 supine position 에서의 PEEP 사용 수준 ($7.8{±}3.2cm$ $H_2O$, $8.6{±}3.5cm$ $H_2O$, p=0.188) 등은 유의한 차이가 없었다. 결 론 : ARDS 환자에서 prone position은 폐산소화지표를 호전시키거나 평균동맥압을 상승시키며 양성 호흡반응 여부는 ARDS 발생 후 조기에 결정되는 것으로 추정되었다.